MRI accurately identifies early murine mammary cancers and reliably differentiates between in situ and invasive cancer: correlation of MRI with histology. (7th July 2015) - Mustafi, Devkumar; Zamora, Marta; Fan, Xiaobing; Markiewicz, Erica; Mueller, Jeffrey; Conzen, Suzanne D.; Karczmar, Gregory S.
<x xml:space="preserve">Abstract</x> MRI methods that accurately identify various stages of mouse mammary cancer could provide new knowledge that may have a direct impact on the management of breast cancer in patients. This research investigates whether we can accurately follow the progression from in situ to invasive cancer by the evaluation of in vivo and ex vivo MRI, and in comparison with histology as the gold standard for the diagnosis and staging of cancer. Six C3(1)SV40Tag virgin female mice, aged 12–16 weeks, were studied. At this age, these mice develop in situ cancer that resembles human ductal carcinoma in situ (DCIS). Fast spin‐echo images of inguinal mammary glands were acquired at 9.4 T. After in vivo MRI, mice were sacrificed; inguinal mammary glands were excised and fixed in formalin for ex vivo MRI. Three‐dimensional, volume‐rendered, in vivo and ex vivo MR images were then correlated with histology. High‐resolution ex vivo scans facilitated the comparison of in vivo scans with histology. The sizes of mammary cancers classified as in situ on the basis of histology ranged from 150 to 400 µm in largest diameter, and the average signal intensity relative to muscle was 1.40 ± 0.18 on T2‐weighted images. Cancers classified as invasive on the basis of histology were >400 µm in largest diameter, and the average intensity relative to muscle on T2‐weighted images was 2.34 ± 0.26. Using a cut‐off of 400 µm in largest diameter to distinguish between in situ and invasive cancers, a T2‐weighted signal intensity of at least 1.4 times that of muscle for in situ cancer, and at least 2.3 times that of muscle for invasive cancer, 96% of in situ and 100% of invasive cancers were correctly identified on in vivo MRI, using histology as the gold standard. Precise MRI–histology correlation demonstrates that MRI reliably detects early in situ cancer and differentiates in situ from invasive cancers in the SV40Tag mouse model of human breast cancer. Copyright © 2015 John Wiley & Sons, Ltd.